Establishing Change Management for Organisational Effectiveness in Architecture Studio - Siahaan, Gita Advenia; Permana, Muhammad Yorga (Journal Research of Social Science, Economics, and Management, 2026)
Architectural studios face ongoing challenges in balancing creativity with business-oriented formalization. This research examines Studio A, an Indonesian architectural studio established in 2010, which has experienced organizational challenges during its growth phase. In recent years, Studio A initiated several organizational changes, including restructuring toward a semi-corporate system and establishing new business units. However, these initiatives have been ineffective, resulting in delayed organizational reform and limited improvements in organizational effectiveness. This study addresses three research questions concerning the gap between current and desired organizational effectiveness, the alignment of Studio A's change process with established frameworks, and strategic actions required to improve organizational reform. Primary data were collected through in-depth interviews and focus group discussions with current and former staff and the principal architect, complemented by benchmarking interviews with comparable studios. Secondary data were obtained from internal documents and relevant literature. The McKinsey 7S framework was used to assess gaps between current and ideal organizational states, while Kotter's 8-step change management framework evaluated the change process. Findings reveal significant gaps across the 7S dimensions, particularly in strategy communication, decision-making autonomy, leadership development, and talent management. The change process analysis indicates weak foundations in the early stages of change management, including an unclear vision and insufficient empowerment. This research recommends strategic actions focused on defining a clear vision, structuring decision-making autonomy, implementing leadership development programs, establishing phased hiring plans, developing structured talent management, and aligning compensation with staff expectations to enhance organizational effectiveness in creative-sector enterprises.